Assessment of 2D:4D ratio for the early diagnosis of caries and malocclusion in 7-15-year-old children - Issrani, Rakhi; Aljohani, Fahad; Prabhu, Namdeo; Alam, Mohammad Khursheed (Bangladesh Journal of Medical Science, 2021)
Background: The ratio between 2nd and 4th digit length is termed as hormonal fingerprintand is used as an indirect marker in many medical diseases.Dental studies pertaining to theimportance of hormonal fingerprint on oral health are very sparse. Aim and objectives: Tostudy the correlation of dental caries and malocclusion with hormonal fingerprints. Materialsand Methods: A total of 100 children of age group 7-15 years and both genders were randomlyselected and included in the present study. The hormonal fingerprint (2D:4D ratio) wasdone bymeasuring the length ratio of the index and ring finger with the help of digital vernier caliper.Caries assessment wascarried out using standard mouth mirrors and Community PeriodontalIndex probes. WHO assessment form (1997) was followed for assessment of dentitionstatus and treatment need.Occlusal characteristics evaluated were molar relation, anteriorand posterior crossbite, open bite, deep bite and lower anterior crowding. The subjects weredivided into high 2D:4D, equal 2D:4D digit ratio and low 2D:4D. All the measurements weredone by two investigators. The data collected were tabulated and statistically analyzed usingChi-square and ANOVA test. Results: Out of 100 children, 34% were males and 66% werefemales. Most of the participants were 7-8 years old (12 males and 15 females). Majority of theparticipants (87% for the right hand and 80% for left hand) had low 2D:4D ratio, only 6% forright and 11% for the left hand had high 2D:4D ratio and the remaining had equal 2D:4D ratio.Statistically insignificantcorrelation between 2D:4D ratio and deft/DMFT score and occlusalstatus of an individualwere found. Conclusion:The insignificant results of 2D:4D ratio with allthe parameters assessed validates that hormonal fingerprints could not be employed as an earlypredictor of caries and malocclusion in an individual. Bangladesh Journal of Medical Science Vol.20(1) 2021 p.154-158